2019
DOI: 10.1111/jpm.12521
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of helpful risk management practices within mental health services. A mixed studies systematic review of primary research

Abstract: Accessible Summary What is known about the subject? Risk in psychiatry involves harm to self or others owing to mental health difficulties, for example iatrogenic effects of treatment, self‐harm, suicide and violence. Risk management is a framework to minimize risks, comprising of risk assessment, generation of risk management plans and evaluation of interventions. Literature has extensively explored risk management and presented a critique that its practices can lead to patient harm. However, there is a pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Deering et al. (2019) systematic review supported the notion of collaboration and relationships within risk management. Their results indicated that service users valued interpersonal relationships, feeling heard, and being part of the process.…”
Section: Introductionmentioning
confidence: 97%
“…Deering et al. (2019) systematic review supported the notion of collaboration and relationships within risk management. Their results indicated that service users valued interpersonal relationships, feeling heard, and being part of the process.…”
Section: Introductionmentioning
confidence: 97%
“…Having an awareness of the factors that might influence clinicians' own risk understanding, such as their current knowledge base, beliefs and attitudes, and relationship with service users, was also deemed important. A recent systematic review (Deering et al, 2019) supports the centrality of building relationships for effective risk management and that service users value interpersonal relationships, feeling heard and being included in the process, which may be important for future PRM recommendations.…”
Section: Discussionmentioning
confidence: 97%
“…Although, Haines et al (2018) do not mention pornography specifically, it is possible that the same process applies. A recent systematic review by Deering et al (2019) explored what patients felt were beneficial with regards to their risk management. They noted that it was important that patients felt involved in the risk management plan in addition to their wider support network, such a families and friends.…”
Section: Decision Making and Risk Managementmentioning
confidence: 99%
“…This, therefore, could improve clinical practice, and allow members of the team to feel valued and important as well as reducing possible biases. Interestingly, none of the participants considered involving the patients in the decision making or risk management process despite research indicating that patients find this beneficial (Deering et al, 2019).…”
Section: Theme Six -Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation